2022
DOI: 10.1177/23259671221076045
|View full text |Cite
|
Sign up to set email alerts
|

ACL Tears in the National Football League From 2013 to 2020: Analysis of the 2020 Season After Delays and Schedule Changes From the Early COVID-19 Pandemic Relative to Prior Seasons

Abstract: Background: The impact of fatigue and preseason preparation on anterior cruciate ligament (ACL) tears in the National Football League (NFL) are not well described. The 2020 NFL season did not include the standard preseason in response to changes secondary to the coronavirus disease-2019 (COVID-19) pandemic. Purpose: To evaluate the association of game play on ACL tears in NFL athletes and to determine if differences in ACL tear epidemiology were present based on season of play from 2013 to 2020. Study Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…9 One study investigating injury incidence during the COVID-19 shortened MLB season demonstrated an increased injury incidence rate compared to the previous season (2020 season: 8.66 per 1000 AEs; 2019 season: 5.13 per 1000 AEs). 3 Previous studies across multiple professional leagues including the National Basketball Association, 10 National Football League, 11,12 European professional soccer leagues, 13 have also reported an increase in injury rates during the 2020 shortened season. However, most of these studies reported comparisons to a single previous season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 One study investigating injury incidence during the COVID-19 shortened MLB season demonstrated an increased injury incidence rate compared to the previous season (2020 season: 8.66 per 1000 AEs; 2019 season: 5.13 per 1000 AEs). 3 Previous studies across multiple professional leagues including the National Basketball Association, 10 National Football League, 11,12 European professional soccer leagues, 13 have also reported an increase in injury rates during the 2020 shortened season. However, most of these studies reported comparisons to a single previous season.…”
Section: Introductionmentioning
confidence: 99%
“…Sparse information is available on previous five season data, which may be more representative of injury rate (IR trends), or on the subsequent 2021 season to determine if IR stabilized the following year. Furthermore, previous injury surveillance literature among professional leagues during the 2020 COVID-19 season reported injuries based on anatomic zones 3 versus recommended standardized reporting by body region/area, 14 or reported on a single pathology, 11 making comparison to previous literature difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, limited literature has been published looking at the effects of COVID-19 on NFL injury rates (1)(2)(3)(30)(31)(32)35). Studies performed by Bailey (2,3,30,35).…”
Section: Introductionmentioning
confidence: 99%
“…However, Platt et al (32) analyzed the 2020 NFL regular season and found no change in overall incidence of injury or incidence of injury by player position compared with previous seasons. Furthermore, Patetta et al and Allahabadi et al analyzed the incidence of anterior cruciate ligament (ACL) tears in the 2020 NFL season (1,31). They found an increase in the incidence of ACL tears during the first weeks of the 2020 regular season; however, when these injuries were compared with the number typically experienced during the preseason, there was no increase (1,31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation